KONTRIBUSI ISLAM TERHDAP PERKEMBANGAN RENAISSANCE DI EROPA - Bakar, Abu (Fakultas Agama Islam, 2022)
Islam, apart from being a divine religion, is also a view of life and life in building world civilization. The success of the Umayyads and Abasiaah was judged by many circles as an inspiration for the progress of the modern world (Globalization). globalization that is happening at this time is sourced from the West, and continue to hold supremacy and hegemony in various fields the life of the world community in general, but Islam as an Inspiration as well as a civilized religion certainly has a major contribution to the progress achieved by The Western country, if so when globalization is sourced from the West, appears with a political-economic character, and science-technology, of course Islam must be able to act as a filter and penetration of the negative impact it causes